Development of a modular photoreactor for the upscaling of continuous flow photochemistry. Issue 11 (30th September 2022) - Hermens, Johannes G. H.; Lepage, Mathieu L.; Kloekhorst, Arjan; Keller, Erik; Bloem, Robin; Meijer, Maurice; Feringa, Ben L.
Abstract : An easily-built, user-friendly modular photoreactor enables optimization and upscaling of flow photooxidation. Abstract : The upscaling of biphasic photochemical reactions is challenging because of the inherent constraints of liquid–gas mixing and light penetration. Using semi-permeable coaxial flow chemistry within a modular photoreactor, the photooxidation of the platform chemical furfural was scaled up to produce routinely 29 gram per day of biobased building block hydroxybutenolide, a precursor to acrylate alternatives.